Driver Scheduling Priority Decision Support System Using the Weighted Product Method - Fati Harmonis Zai; Desman Karya Jaya Zega; Fadlina; Fince Tinus Waruwu (Jurnal Armada Informatika, 2026)
Driver scheduling is an important process in public transportation operations because it is related to workload distribution, fleet readiness, and service quality. At Koperasi Pengangkutan Umum Medan (KPUM), driver scheduling priorities are still determined conventionally, making decisions potentially subjective and difficult to trace quantitatively. This study aims to develop a web-based Decision Support System (DSS) to determine driver scheduling priorities using the Weighted Product method. The assessment criteria consist of route mastery, discipline, work experience, working time, and health condition. Data were obtained through observation, interviews, and internal assessment of ten active drivers. The analysis process includes weight normalization, construction of compatibility ratings, S vector calculation, V vector calculation, and alternative ranking. The calculation results show that alternative A8, Binarto, obtains the highest preference value of 0.1311, followed by A5 with 0.1265 and A9 with 0.1234. Functional testing indicates that the login feature, data management, calculation process, and ranking display run according to the test scenarios. The proposed system can assist KPUM in preparing scheduling priorities in a faster, measurable, and more transparent manner.